Disulfide Bond Replacement with 1, 4‐ and 1, 5‐Disubstituted [1, 2, 3]‐Triazole on C‐X‐C Chemokine Receptor Type 4 (CXCR4) Peptide Ligands: Small Changes that Make Big Differences. Issue 44 (20th July 2020) - Tomassi, Stefano; Trotta, Anna Maria; Ieranò, Caterina; Merlino, Francesco; Messere, Anna; Rea, Giuseppina; Santoro, Federica; Brancaccio, Diego; Carotenuto, Alfonso; D'Amore, Vincenzo Maria; Di Leva, Francesco Saverio; Novellino, Ettore; et al.
Abstract: Here we investigated the structural and biological effects ensuing from the disulfide bond replacement of a potent and selective C‐X‐C chemokine receptor type 4 (CXCR4) peptide antagonist, with 1, 4‐ and 1, 5‐ disubstituted 1, 2, 3‐triazole moieties. Both strategies produced candidates that showed high affinity and selectivity against CXCR4. Notably, when assessed for their ability to modulate the CXCL12‐mediated cell migration, the 1, 4‐triazole variant conserved the antagonistic effect in the low‐mid nanomolar range, while the 1, 5‐triazole one displayed the ability to activate the migration, becoming the first in class low‐molecular‐weight CXCR4 peptide agonist. By combining NMR and computational studies, we provided a valuable model that highlighted differences in the interactions of the two peptidomimetics with the receptor that could account for their different functional profile. Finally, we envisage that our findings could be translated to different GPCR‐interacting peptides for the pursuit of novel chemical probes that could assist in dissecting the complex puzzle of this fundamental class of transmembrane receptors. Abstract : Disulfide bond replacement with a 1, 4‐ and 1, 5‐ [1, 2, 3]‐triazole bridge represents a valuable strategy for improving the structural variability of GPCR‐interacting peptides providing novel chemical tools that could assist in dissecting the complex puzzle of GPCR signaling.